Memaknakan terjemahan frasa sendi bahasa Arab ke bahasa Melayu berdasarkan ilmu sintaksis-semantik - Ismail Muhamad; Azman Che Mat (Penerbit Universiti Kebangsaan Malaysia, 2010)
This article revolves around the translation of Shibh al-Jumlah in Arabic and Malay language. The focus of the study is on syntax and semantics. Data for the research were gathered from the Holy Koran. Using a descriptive approach as the research instrument, a careful analysis was carried out in accordance with the research framework that has been built. The research framework comprised the aspects of syntax and semantics, as well as the principles of translation. The findings of this study suggest some important aspects that require emphasis in the process of translating the Shibh al-Jumlah structure from the Arabic language into the Malay language. Among these were the inherent need to understand aspects of the syntactic and semantic structures of the Arabic sentence in general and also the Shibh al-Jumlah structure specifically. This study had also scrutinized the application of the translation of the Communicative and Dynamic Equavalence of the Shibh al-Jumlah structure. In essence, the findings of the study will futher encourage more in-depth studies towards establishing the field of Arabic-Malay translation.